Optimization of Emergence Profile of Implant Prosthesis: A Literature Review - Minoru Sanda; Daisuke Sato; Kazuyoshi Baba (Faculty of Dentistry, Trisakti University, 2018)
In order to achieve esthetically optimal outcome with implant prosthesis, appropriate topography of emergence profile is crucial. The objective of this review is to explorer current evidence regarding this topic and relevant issue. Extent of interproximal papilla is determined not by the shape of emergence profile but the length between interproximal alveolar bone prominence and interproximal contact of crowns. There have been concerned that multiple times of disconnection and reconnection of abutment enhance peri-implant marginal bone loss, but it’s certified not to be a clinically significant level. Current digital workflow makes this step faster and easier, by copying emergence profile of contralateral tooth or extracted teeth.